2016
DOI: 10.1038/srep36216
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation changes in the globular head of H3N2 influenza hemagglutinin modulate receptor binding without affecting virus virulence

Abstract: Since the emergence of human H3N2 influenza A viruses in the pandemic of 1968, these viruses have become established as strains of moderate severity. A decline in virulence has been accompanied by glycan accumulation on the hemagglutinin globular head, and hemagglutinin receptor binding has changed from recognition of a broad spectrum of glycan receptors to a narrower spectrum. The relationship between increased glycosylation, binding changes, and reduction in H3N2 virulence is not clear. We evaluated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…Accretion of conformationally flexible oligosaccharides on the HA further shields the antigenic sites to facilitate immune evasion [43, 5962]. Nonetheless, the added N-glycosylation sites can also affect binding of the natural receptor when they are proximal to the RBS [54, 6367]. The functional constraints of the RBS render it difficult, if not impossible, to be completely shielded by oligosaccharides.…”
Section: Antigenic Drift: Point Mutations and Glycosylationmentioning
confidence: 99%
“…Accretion of conformationally flexible oligosaccharides on the HA further shields the antigenic sites to facilitate immune evasion [43, 5962]. Nonetheless, the added N-glycosylation sites can also affect binding of the natural receptor when they are proximal to the RBS [54, 6367]. The functional constraints of the RBS render it difficult, if not impossible, to be completely shielded by oligosaccharides.…”
Section: Antigenic Drift: Point Mutations and Glycosylationmentioning
confidence: 99%
“…Alymova et al [66] also recently examined H3N2 with varying glycosylation levels, and concluded that glycosylation of the HA1 could decrease binding affinity, without reducing virulence. They further introduced the hypothesis, based on the consistent binding of the HAs to linear α2-6 sialylated polylactosamine glycans, that physiologically relevant receptor binding had not changed over the past 40 years.…”
Section: Impact Of Ha Glycosylation On Specificitymentioning
confidence: 99%
“…HA surface antigenicity is affected strongly by the presence and types of N-glycosylation, which cannot be predicted from genetic sequence or 3D protein coordinates (13). N-Glycosylation sequons accumulate in the protein sequence, giving rise to increasing glycosylation as the strain evolves, shielding of antigenic sites (8,14,15), influencing receptor binding (16,17) and binding to innate immune system molecules (18,19).…”
Section: Introductionmentioning
confidence: 99%